Synthesis and Structure-Activity Relationship Studies of HIV-1 Virion Infectivity Factor (Vif) Inhibitors that Block Viral Replication - Ali, Akbar (2012)
The HIV-1 Vif protein, essential for in vivo viral replication, protects the virus from innate antiviral cellular factor APOBEC3G (A3G), and is an attractive target for developing antiviral therapeutics. Here we have evaluated the structure-activity relationships of RN18, a small molecule recently identified as an inhibitor of Vif function that blocks viral replication only in non-permissive cells expressing A3G, by inhibiting Vif-A3G interactions. Microwave-assisted cross-coupling reactions were developed to prepare a series of RN18 analogues with diverse linkages and substitutions on the phenyl rings. A dual cell-based assay system was used to assess antiviral activity against wild-type HIV-1 in both non-permissive (H9) and permissive (MT-4) cells that also allowed evaluation of specificity. In general, variations of phenyl substitutions were detrimental for antiviral potency and specificity, but isosteric replacements of amide and ether linkages were relatively well tolerated. These SAR data define structural requirements for Vif-specific activity, identify new compounds with improved antiviral potency and specificity, and provide leads for further exploration to develop new antiviral therapeutics.